The effects of a postural supporting "New Nesting Device" on early neurobehavioral development of premature infants. Issue 3 (June 2021) - Tang, Xiaoli; Bei, Fei; Sha, Sha; Qin, Yanmin
Abstract: Background: Extended positioning is believed to have negative impacts on the neurodevelopment of the infants. Currently, many neonatal intensive care unit (NICU) in China do not have adequate posture supporting device for premature infants. Positional support has been done often by using bed sheet, washcloth or blanket. Inadequate posture support can hinder the neurobehavioral development of premature infants. Purpose: The study aims to compare the effects of neurobehavioral development outcomes between a "New Nesting Device" and a "Traditional-Nest" posture supporting interventions, for premature infants from NICU admission to 36th week of gestational age after birth. Methods: The study followed the Quasi-experimental study design. A total of 95 participants were randomized to either a "New Nesting Device" group (n = 49) or "Traditional-Nest" group (n = 46) after admission. All participating premature infants were assessed at 34th and 36th weeks of gestational age, and posture, body movements and early neurobehavioral outcomes were measured. Posture and body movements were recorded once at 34th weeks and again at 36th weeks. Digital video camera was used at the bedside to record an uninterrupted 12-h-long session to obtain posture and behavioral data. All participating premature infants received aEEG and cranial ultrasonography examinations at bedside to evaluate early neurobehavioral outcomes when they reached 34th weeks and again 36th weeks of gestational age. Results: The "New Nesting Device" group had better effects on posture (p＜0.001 for both), and demonstrated more smooth body movements (p = 0.018, p＜0.001) than premature infants of the "Traditional-Nest" group at both 34th and 36th weeks of gestational age. The "New Nesting Device" group also captured higher frequencies of "sleep-wake cycling" (p = 0.049, p = 0.037) through aEEG examination compared to the "Traditional-Nest" group at 34th and 36th weeks of gestational age. Conclusions: "New Nesting Device" can provide premature infants a comfortable posture support similar to the flex posture they had while in the uterus. Smooth body movements and non-extended extremities can promote early neurobehavioral development. This study demonstrates the effects of the newly designed posture support device on premature infants. It also introduced the features of the newly designed nesting device for clinical nurse to understand how the nesting device can enhance comfort and support the neurobehavioral development of premature infants. Implications for practice and research: Further research is needed to determine the cost and long-term effect contribution to the overall neurobehavioral development of premature infants by continued use of this soothing posture support device after discharge from NICU. The study also provides reference for the selection of posture supporting intervention and outcome measurements for future similar clinical studies.